The Importance of Environmental Education in Biology Learning to Increase Students' Environmental Awareness - Cartono Cartono (Jurnal Info Sains : Informatika dan Sains, 2022)
The importance of environmental awareness in modern society demands education that focuses on a deep understanding of ecosystems and environmental responsibility. This research aims to explore the role of environmental education in biology learning as an effort to increase students' awareness of protecting the environment. The research method used is descriptive qualitative. The research results show that the integration of Environmental Education in biology learning is effective in increasing students' understanding of biological concepts while developing their awareness of environmental issues. Students not only gain theoretical knowledge, but also directly experience environmental aspects through practical experiences such as observations, experiments in the field, and related activities. This awareness then forms a responsible attitude towards the environment, encouraging students to take positive action in maintaining the sustainability of nature. The research results provide empirical support for the effectiveness of this approach in creating students who are not only scientifically educated, but also have relevant life skills and are ready to play a role in preserving the global environment.